DNX-2401, an Oncolytic Virus, for the Treatment of Newly Diagnosed Diffuse Intrinsic Pontine Gliomas: A Case Report - Tejada, Sonia; Díez-Valle, Ricardo; Domínguez, Pablo D.; Patiño-García, Ana; González-Huarriz, Marisol; Fueyo, Juan; Gomez-Manzano, Cande; Idoate, Miguel Angel; Peterkin, Joanna; Alonso, Marta M. (Frontiers in Oncology, 2018)
Diffuse Intrinsic Pontine Gliomas (DIPGs) are aggressive glial brain tumors that generally affect children, for which there is no curative treatment. Median overall survival is only one year. Currently, the scientific focus is on expanding the knowledge base of the molecular biology of DIPG, and identifying effective therapies. Oncolytic adenovirus DNX-2401 is a replication-competent, genetically modified virus capable of infecting and killing glioma cells, and stimulating an anti-tumor immune response. Clinical trials evaluating intratumoral DNX-2401 in adults with recurrent glioblastoma have demonstrated that the virus has a favorable safety profile and can prolong survival. Subsequently, these results have encouraged the transition of this biologically active therapy from adults into the pediatric population. To this aim, we have designed a clinical Phase I trial for newly diagnosed pediatric DIPG to investigate the feasibility, safety and preliminary efficacy of delivering DNX-2401 into tumors within the pons following biopsy. This case report presents a pediatric patient enrolled in this ongoing Phase I trial for children and adolescents with newly diagnosed DIPG. The case involves an 8-year-old female patient with radiologically diagnosed DIPG who underwent stereotactic tumor biopsy immediately followed by intratumoral DNX-2401 in the same biopsy track. Because there were no safety concerns or new neurological deficits, the patient was discharged 3 days after the procedures. To our knowledge, this is the first report of intraumoral DNX-2401 for a patient with DIPG in a clinical trial. We plan to demonstrate that intratumoral delivery of an oncolytic virus following tumor biopsy for pediatric patients with DIPG is a new feasible approach and that DNX-2401 represents a novel treatment for the disease.